Direct‐acting antiviral therapy decreases hepatocellular carcinoma recurrence rate in cirrhotic patients with chronic hepatitis C. (25th May 2017) - Virlogeux, Victor; Pradat, Pierre; Hartig‐Lavie, Kerstin; Bailly, François; Maynard, Marianne; Ouziel, Guillaume; Poinsot, Domitille; Lebossé, Fanny; Ecochard, Marie; Radenne, Sylvie; Benmakhlouf, Samir; Koffi, Joseph; et al.
Abstract: Background and Aims: Arrival of direct‐acting antiviral agents against hepatitis C virus with high‐sustained virological response rates and very few side effects has drastically changed the management of hepatitis C virus infection. The impact of direct‐acting antiviral exposure on hepatocellular carcinoma recurrence after a first remission in patients with advanced fibrosis remains to be clarified. Methods: 68 consecutive hepatitis C virus patients with a first hepatocellular carcinoma diagnosis and under remission, subsequently treated or not with a direct‐acting antiviral combination, were included. Clinical, biological and virological data were collected at first hepatocellular carcinoma diagnosis, at remission and during the surveillance period. Results: All patients were cirrhotic. Median age was 62 years and 76% of patients were male. Twenty‐three patients (34%) were treated with direct‐acting antivirals and 96% of them achieved sustained virological response. Median time between hepatocellular carcinoma remission and direct‐acting antivirals initiation was 7.2 months (IQR: 3.6‐13.5; range: 0.3‐71.4) and median time between direct‐acting antivirals start and hepatocellular carcinoma recurrence was 13.0 months (IQR: 9.2‐19.6; range: 3.0‐24.7). Recurrence rate was 1.7/100 person‐months among treated patients vs 4.2/100 person‐months among untreated patients ( P =.008). In multivariate survival analysis, the hazard ratio for hepatocellular carcinoma recurrence after direct‐acting antivirals exposure was 0.24 (95% confidence interval: 0.10–0.55; P <.001). Conclusions: Hepatocellular carcinoma recurrence rate was significantly lower among patients treated with direct‐acting antivirals compared with untreated patients. Given the potential impact of our observation, large‐scale prospective cohort studies are needed to confirm these results. Abstract : See Editorial on Page1110